(untitled) (PlaySpace, 2024)
The digital music theory admission test for higher music education in Norway uses two alternative symbol systems for harmony analysis. In the view adopted here, both systems are unnecessarily complex for an admission test, where a lower level of theoretical knowledge would suffice. In addition, both systems focus on the so-called Euroclassical music tradition and largely ignore the conventions of other musical styles. Moreover, the literature suggested for candidates preparing for the test is not properly aligned with the test. This article outlines the harmony tasks in the admission test, discusses issues with the test design, reviews the literature suggested for candidates, and explores the symbol systems used in the test. As a proposal for development, the article suggests that a different analysis system be used for the test.